UNDERSTANDING THE ROLE OF METACOGNITIVE SKILLS IN FOSTERING CRITICAL THINKING AMONG STUDENTS IN HIGHER EDUCATION AT UNIVERSITY OF AGRICULTURE, FAISALABAD - Ayesha Ismail; Aqeela Saghir; Muhammad Rafay Muzamil; Sadia Ghulam Rasool; Nasira Farid; Tahmina Khalid; Rabia Yousaf (International Journal of Contemporary Issues in Social Sciences, 2023)
This research paper aims to explore the significance of metacognitive skills in fostering critical thinking among students in higher education. It highlights the importance of metacognitive training as a means to empower students with the necessary cognitive tools for academic success and lifelong learning. Critical thinking is crucial competency in the current knowledge-based economy and universities play a pivotal role in developing this skill in their students. This paper was analyzed the existing literature on the subject, discussed the theoretical framework and proposed practical strategies for educators to incorporate metacognitive practices in teaching methodologies to nurture critical thinking in higher education. For this purpose, 135 participants were conveniently selected out of 432 from M.Phil. (Education (weekend) program in University of Agriculture Faisalabad. A well-structured, valid and pretested questionnaire was used to collect data. The data were analyzed with the help of SPSS. Arithmetic Mean, standard deviation and percentages were being calculated to explain the results. While bivariate analysis through chai-square test was taken to check the correlation of variables. Increase the collaboration between students and teachers, increase understanding, develop confidence for explanation of topic, increase the multi linguistic skills, increase active participation of the students, enhance students’ knowledge and skills and develop thinking skills in students to attain maximum grades were the major points as perceived by the respondents. According to the findings, metacognition, the ability to monitor, regulate and direct one’s own thinking processes, had been identified as an essential factor in enhancing critical thinking capabilities. So, the collaboration between students and teacher is very important to improve the metacognitive skills in students. The institutions and administrators also take the responsibility for this process.